Peaceful dying among Canada's elderly: An analysis of the Canadian Longitudinal Study on Aging. - Komal Aryal; Aaron Jones; Peter Tanuseputro; Lauren E Griffith; Paul C Hebert; Susan Kirkland; Deborah J Cook; Andrew P Costa (PLoS ONE)
Introduction Death is universal, yet relatively little is known about how Canadians experience their death. Using novel decedent interview data from the Canadian Longitudinal Study on Aging we describe the prevalence and characteristics of peace with dying among older Canadians. Methods We conducted a secondary analysis of decedent interview data from the Canadian Longitudinal Study on Aging. Proxies of deceased Canadian Longitudinal Study on Aging participants reported on participants' end-of-life experiences between January 2012 to March 2022. We examined end-of-life characteristics and their association with proxy reports of experiencing peace with dying. We conducted regression analysis to explore the association between demographic and end-of-life characteristics and experiencing peace with dying. Results Of 3,672 deceased participants, 1,287 (35.0%) had a completed decedent questionnaire and were included in the analysis. Respondents reported that two-thirds (66.0%) of the deceased experienced peace with dying and 17% did not experience peace with dying. The unadjusted odds of experiencing peace with dying were higher for those with an appointed power of attorney (OR 1.80; CI 1.39-2.33), those who died of cancer (OR 1.71; CI 1.27-2.30), those in hospice/receiving palliative care (OR 1.67; CI 1.19-2.37), individuals older than 75 years (OR 1.55; CI 1.04-2.30), or widowed (OR 1.53; CI 1.12-2.10). Widowhood (OR 1.51; CI 1.01-2.29), having an end-of-life SDM (OR 1.58; CI 1.14-2.17), and dying of cancer (OR 1.67; CI 1.19-2.23) increased the adjusted odds of dying with peace. Conclusions Close to 1 in 5 older Canadians may not experience peace with dying, which supports greater focus on improving the end-of-life care. Our findings suggest that advanced planning may enhance the experience of a peaceful death in Canada.